Career Growth as Factor of Personnel Motivation in Systems of Today’s Organization Management - A. V. Galaktionov (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The article studies sources of professional education impact on successfulness of career growth, which underlies organizational motivation; substantiates approaches to building education trajectories creating competitive advantage on labour market and puts forwards an ideal model of career growth worked out with regard to education levels, professional standard levels and the work-related line of an abstract organization. The author provided recommendations on shaping well-balanced motivation of experts of organization management system. The research was done with due regard to requirements of the professional standard ‘Management (Control) of the Organization’. The problem of career growth management was considered only for the category of administrativemanagerial personnel or managers, i.e. functional experts of the system of organization management. To process information, substantiate problems and obtain results of the present research the author used methods of comparative analysis, grouping, sociological investigations, as well as historic method and method of complex analysis and synthesis.